Letramento Digital e Formação de Professores: uma análise crítica das práticas digitais de professores de línguas em formação inicial - Pereira, Amanda Mendonça (2020)
The main objective of this work is to investigate, through the analysis of the digital practices of language teachers in initial training at a Public University of Minas Gerais, the digital literacy types that these teachers use. This research presents a theoretical framework that contextualizes questions related to studies in Applied Linguistics on teacher education, a field where this research is inserted, seeking to establish a relationship with public policies that govern the use of digital technologies in schools and also with studies on Digital Literacy and Initial Teacher Training. In order to meet the objective of this work, the research was carried out with forty (40) students of the 8th period of Language Course, enrolled in the subject of Information and Communication Digital Technologies in teaching English language. The methodology used is characterized qualitatively, delineated through an exploratory approach and case study. Four data generation instruments were used for the research – the initial questionnaire, the analysis of the virtual discussion forums, the face-to-face observation during the microteaching activity and the final questionnaire. The data collected during this research were treated taking as an analysis category the table of digital literacy types proposed by Dudeney, Hockly and Pegrum (2016) and also the TPACK table of Mishra and Koeler (2006). The results show that the participants had, at the beginning of the subject, skills related to network literacy and personal literacy, according to the table of digital literacy types by Dudeney, Hockly and Pegrum (2016), since their digital practices pointed to a use of digital technologies at the personal level, with constant access to social networks. After having studied the aforementioned subject, it was possible to notice that the participants acquired skills related to literacy in games, multimedia literacy and literacy in filtering, literacies that are related to the pedagogical use of digital technologies. Thus, it was possible to conclude that the teacher training course assisted in the process of developing the digital literacy of future teachers, since throughout the analyzed course the participants acquired new skills related to the digital literacies of Dudeney, Hockly and Pegrum (2016). However, it was possible to notice, after the four phases of the analysis performed in this work, that it is still necessary to have greater incentive regarding the use of digital technologies throughout the initial training course, as well as a direct contact with them by the students so that it is possible to contemplate more skills of the different literacies.